Optimizing Social Media Platforms for Enhanced Distance Learning Support Systems: A Case Study of Universitas Terbuka - Setyo Kuncoro; Abdurrahman Rahim Thaha (PT ARRUS Intelektual Indonesia, 2023)
The rapid evolution of information and communication technology (ICT) has revolutionized education, particularly in the context of distance learning. Social media has emerged as a crucial component in the educational landscape, offering opportunities for collaboration and interaction. This article explores the optimization of social media platforms to enhance distance learning support systems, focusing on the case of Universitas Terbuka, a renowned institution for Open Distance Learning (ODL) programs. The study employs the UTAUT model to investigate the factors influencing the voluntariness of social media use for distance learning. Through a quantitative research design involving 233 respondents, Structural Equation Modeling (SEM) is used to analyze the relationships between variables. The findings reveal that factors such as effort expectancy, social influence, and facilitating conditions significantly impact students' willingness to use social media for distance learning. These results suggest the importance of fostering social influence and ease of use expectations to enhance the distance learning experience at Universitas Terbuka and similar institutions. Overall, this study underscores the transformative potential of social media in education and its role in shaping the future of learning environments.